Electric vehicles and charging infrastructure in Turkey: An overview. (June 2021) - Gönül, Ömer; Duman, A. Can; Güler, Önder
Abstract: The depletion of fossil resources, energy dependency, increase in fuel costs and environmental concerns caused by fossil fuel vehicles, along with the advances in battery technology and their manufacturing processes have promoted a transition towards electric vehicles (EV). Depending on inner and external factors, some countries fastly adopted the new technology, whereas others act more slowly. In this study, an overview of Turkey's position in EV technology is presented. The current EV, charging infrastructure, and battery market, as well as EV-related regulations, research and development (R&D) activities, and industry in the country are evaluated. An EV charging station (EVCS) density map of Turkey is formed to illustrate the deficiencies in the existing charging infrastructure. The challenges and opportunities in the country are discussed and presented in the form of a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis and the study is concluded with a list of recommendations. Currently, the public in Turkey is focused on the state-supported "local brand EV" project. However, the acceptance of EVs is still low in the country. To that end, social awareness-raising activities, especially electric public transportation and electric public fleets, should be promoted for EVs to achieve their higher visibility. The EVCS infrastructure should be further expanded in the eastern part of Turkey and further steps should be taken regarding EV/EVCS-related incentives. Highlights: The current status of EVs and EVCSs in Turkey are introduced. EV-related regulations, researches, and industry are examined. EVCS density map is created for Turkey. A cost comparison between EV charging and ICEV refueling is made. The challenges and opportunities are discussed and recommendations are presented.